Зміна фазового складу синтетичних магнетовпорядкованих наночастинок оксидів і гідроксидів заліза з різними покриттями за даними Мессбауерової спектроскопії - Шевчук, В.Н.; Попович, Д.І.; Белюх, В.М.; Усатенко, Ю.М.; Іваницький, В.П.; Брик, О.Б.; Дудченко, Н.О.; Польшин, Е.В.; Редько, Я.В. (Наносистеми, наноматеріали, нанотехнології, 2013)
За допомогою методи Мессбауерової спектроскопії на ядрах ⁵⁷Fe вивчено
фазовий склад синтетичних магнетовпорядкованих наночастинок з біоадаптованими покриттями та процес їх «старіння» після зберігання зразків в умовах навколишнього середовища впродовж 2,5 років. Серед фаз,
які співіснують у наночастинках, виявлено магнетит, маггеміт і гетит.
Встановлено, що «старіння» наночастинок проявляється в окисненні магнетиту, який є домінантною фазою, і в утворенні самостійної фази – маггеміту. С помощью метода мёссбауэровской спектроскопии на ядрах ⁵⁷Fe изучен
фазовый состав синтетических магнитоупорядоченных наночастиц с биоадаптированными покрытиями и процесс их «старения» после хранения
образцов в условиях окружающей среды на протяжении 2,5 лет. Среди
фаз, сосуществующих в наночастицах, установлены: магнетит, маггемит
и гетит. Установлено, что «старение» наночастиц проявляется в окислении магнетита, который является доминирующей фазой, и в образовании
самостоятельной фазы – маггемита. Phase composition of synthesized magnetically ordered nanoparticles with
biocompatible coverings and the process of their ‘ageing’ after storage under
environmental conditions during 2.5 years are studied by means of the ⁵⁷Fe
Mössbauer spectroscopy. As found, the phases coexisting in nanoparticles are
magnetite, maghemite and goethite. Each sample has individual phase composition. As determined, the ‘ageing’ of nanoparticles appears in oxidation of
magnetite that is a dominant phase and in formation of separate phase–
maghemite. Goethite formation is not observed, during the process of samples’
‘ageing’, but its quantity increase insignificantly in ‘aged’ samples as
compared to initial samples. The cause of magnetite oxidation could be excess
oxygen ions, hydroxyl groups and chemically bounded water, which could be
the result of nanoparticles’ synthesis by precipitation method. The covering
of developed high-imperfect surface of nanoparticles by biocompatible materials
does not eliminate the possibility of diffusion of oxidants from environment.
Obtained results could be used for improvement of synthesis technologies
of environmentally stable magnetically ordered nanoparticles with
predetermined properties.